Quantum mechanics: principles and formalism - McWeeny, R. (International encyclopedia of physical chemistry and chemical physics. (Oxford). Classical and quantum mechanics, 1972)
Quantum Mechanics: Principles and Formalism gives importance to the exposition of the fundamental bases of quantum mechanics. This text first discusses the physical basis of quantum theory. This book then provides some simple solutions of SchrAdinger's equation, eigenvalue equations, and general formulation of quantum mechanics. The general theory of representations is also tackled. In discussing this topic, this text specifically looks into the harmonic oscillator, Dirac notation, time-evolution, SchrAdinger equation in momentum space, and transformation theory. This publication will be inv.